A more precise, repeatable and diagnostic alternative to surface electromyography – an appraisal of the clinical utility of acoustic myography. (2nd March 2017) - Harrison, Adrian P.
Summary: Acoustic myography (AMG) enables a detailed and accurate measurement of those muscles involved in a particular movement and is independent of electrical signals between the nerve and muscle, measuring solely muscle contractions, unlike surface electromyography (sEMG). With modern amplifiers and digital sound recording systems, measurements during physical activity both inside and outside a laboratory setting are now possible and accurate. Muscle sound gives a representation of the work of each muscle group during a complex movement, and under certain forms of movement even reveals both concentric and eccentric activity, something that sEMG is incapable of. Recent findings suggest that AMG has a number of advantages over sEMG, being simple to use, accurate and repeatable as well as being intuitive to interpret. The AMG signal comprises three physiological parameters, namely efficiency/coordination (E‐score), spatial summation (S‐score) and temporal summation (T‐score). It is concluded that modern AMG units have the potential to accurately assess patients with neuromuscular and musculoskeletal complaints in hospital clinics, home monitoring situations as well as sports settings.